The Malaysiana conference collection of the University of Malaya library: The first phase - Zainab, A.N. (Perpustakaan Universiti Malaya, 1988)
The first phase in the establishment of the Malaysiona Conference Collection began in 7984 and involved locating and collating all proceedings of conferences held locally and papers concerning Malaysia for those held abroad which were already available within the Main Library and bringing them into a special 'Conference Collection' kept within the National Collection Division (NCD) for reference purposes. Simultaneously, form letters were also sent out to request for proceedings of conferences currently held within the country. All papers of these conferences are indexed according to thei: subject matter and the subject cards filed in the 'Conference Index Card Catalogue' kept outside the NCD. Figures based on statistics compiled in December 7987 showed that there were' 2076 titles of conferences in the Collection which contained about 20,000 papers. Figures also showed that borrowing from this Collection has steadily increased since July 7984, which clearly indicated the usefulness of this collec tion as a source of reference for undergraduates and researchers alike.